PENGARUH PENERAPAN MODEL PEMBELAJARAN RELATING, EXPERIENCING, APPLYING, COOPERATING, TRANSFERRING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 1 SOLOK - Shavira, Febrilia Ayu (Jurnal Edukasi dan Penelitian Matematika, 2024)
A person's skills in solving mathematical problems have become an essential component in mathematics learning. However, initial test data on problem-solving competence from students at SMP Negeri 1 Solok, particularly in grade VIII, indicate that these skills need improvement. In this case, the implementation of the REACT learning model can be beneficial. This research examines the impact of using the REACT learning model on students' proficiency in solving mathematical problems. The research was conducted using a quasi-experiment with a Posttest-Only Control Group Design. The hypothesis test yielded a P-value of 0.000, indicating the rejection of H0. This result shows that the REACT learning model significantly influences on students' competence to solve mathematical problems in grade VIII at SMP Negeri 1 Solok.Keywords– Competence in solving mathematical problems, REACT Learning Model, Conventional Learning Model